British Literature I Anthology From the Middle Ages to Neoclassicism and the Eighteenth Century - Robinson, Bonnie J.; Getty, Laura J. (Open textbook library., 2018)
The University of North Georgia Press and Affordable Learning Georgia bring you British Literature I: From the Middle Ages to Neoclassicism and the Eighteenth Century. Featuring over 50 authors and full texts of their works, this anthology follows the shift of monarchic to parliamentarian rule in Britain, and the heroic epic to the more egalitarian novel as genre. Features: Original introductions to The Middle Ages; The Sixteenth Century: The Tudor Age; The Seventeenth Century: The Age of Revolution; and Neoclassicism and the Eighteenth Century Over 100 historical images Instructional Design, including Reading and Review Questions and Key Terms Forthcoming ancillary with open-enabled pedagogy, allowing readers to contribute to the project This textbook is an Open Access Resource. It can be reused, remixed, and reedited freely without seeking permission.